HTR1B genotype and psychopathy: Main effect and interaction with paternal maltreatment. (October 2022) - Palumbo, Sara; Mariotti, Veronica; Vellucci, Stefano; Antonelli, Klizia; Anderson, Nathaniel; Harenski, Carla; Pietrini, Pietro; Kiehl, Kent A.; Pellegrini, Silvia
Abstract: Psychopathy is a condition characterized by atypical emotions and socially maladaptive behavioral patterns. Among incarcerated people, psychopathy has been associated with higher rates of crimes, recidivism, and resistance to treatment. Many studies have indicated significant heritability of psychopathic traits, but little is known about the specific contribution of genes and their interaction with adverse experiences in life. Considering the primary role that serotonin plays in cognition and emotion, we investigated TPH2-rs4570625, 5-HTTLPR, MAOA-uVNTR, HTR1B-rs13212041 and HTR2A-rs6314 as risk factors for psychopathy in the largest sample of institutionalized individuals studied so far, consisting of 793 US White male incarcerated adults, and in a replication sample of 168 US White male incarcerated adolescents. In a subgroup of the adult sample, the interaction between genetics and parenting style, assessed by the Measure of Parental Style (MOPS) questionnaire, was also evaluated. The HTR1B-rs13212041-T/T genotype, as compared to HTR1B-rs13212041-C allele, predicted higher psychopathy scores in both the adult and the adolescent samples. The interaction between HTR1B-rs13212041-T/T genotype and paternal MOPS scores, investigated in a subgroup of the adult sample, was an even stronger predictor of higher levels of psychopathy than either the genetics or the environment taken individually. Overall, these data, obtained in two independent samples, shed new light on neurobiological correlates of psychopathy with promising implications both at a clinical and forensic level. Highlights: Psychopathy has been associated with higher rates of crimes and recidivism. Little is known about the role of genes and early life experiences in psychopathy. Serotonin (5-HT) modulates emotions and cognition, both disrupted in psychopathy. 5-HT genes and parental styles were assessed in two samples of incarcerated males. HTR1B genotype predicted psychopathy and vulnerability to paternal maltreatment.